A transfer learning-basedrecommender system - AYA SAHRAOUI (My University, 2024)
Transformers have revolutionized the field of Automatic Data Processing Natural Language (NLP) producing remarkable results In this study, we propose an extension of this success by introducing A new recommendation system based on Transformers. We exploited their ability to capture complex relationships between data to provide insights precise and personalized recommendations. Using extracted data from Amazon, we conducted an in-depth experiment to evaluate the effectiveness of our recommendation model. The results demonstrated the relevance and effectiveness of our approach, highlighting the advantage of transfer learning in improving recommendation performance. This research opens new perspectives in the field of systems of recommendation by exploiting recent advances in NLP to provide more precise and relevant recommendations to users. ------------------------------------------------------------------------------ لقد أحدثت المحولات ثورة في مجال المعالجة التلقائية للبيانات اللغة الطبيعية (NLP) تحقق نتائج ملحوظة في هذه الدراسة، نقترح تمديد هذا النجاح من خلال تقديم جديد نظام التوصية على أساس المحولات. لقد استغلناهم القدرة على التقاط العلاقات المعقدة بين البيانات لتقديم رؤى توصيات دقيقة وشخصية. باستخدام البيانات المستخرجة من أمازون، أجرينا تجربة متعمقة للتقييم فعالية نموذج التوصية لدينا. وأظهرت النتائج أهمية وفعالية نهجنا، وتسليط الضوء على ميزة نقل التعلم في تحسين أداء التوصية. يفتح هذا البحث آفاقا جديدة في مجال نظم التوصية من خلال استغلال التطورات الحديثة في البرمجة اللغوية العصبية لتقديمها توصيات أكثر دقة وذات صلة للمستخدمين. ------------------------------------------------------------------------------ Les Transformers ont révolutionné le domaine du Traitement Automatique du Langage Naturel (NLP) en produisant des résultats remarquables Dans cette étude, nous proposons une extension de cette réussite en introduisant UN nouveau système de recommandation basé sur les Transformers. Nous avons exploité leur capacité à capturer les relations complexes entre les données pour proposer des recommandations précises et personnalisées. En utilisant des données extraites d'Amazon, nous avons mené une expérimentation approfondie pour évaluer l'efficacité de notre modèle de recommandation. Les résultats ont démontré la pertinence et l'efficacité de notre approche, mettant en évidence l'avantage du transfert d'apprentissage dans l'amélioration des performances de recommandation. Cette recherche ouvre de nouvelles perspectives dans le domaine des systèmes de recommandation en exploitant les avancées récentes en NLP pour fournir des recommandations plus précises et pertinentes aux utilisateurs.